An “Indian” American Congressman: Dalip Singh Saund’s Indian Heritage and His 1956 Journey to Congress - Bhadrajee S. Hewage (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2021)
Indian Americans have managed to become one of the most successful minority communities in the United States. With the rise of politicians such as Kamala Harris, Nikki Haley, and Bobby Jindal, Indian Americans have also reached the upper echelons of U.S. political life. Yet half a century ago, a very different picture emerges. Coming to the U.S. just three years after the 1917 Immigration Act which effectively barred Asian immigration, Dalip Singh Saund progressed from student to citizen to the U.S.’s first Asian Congressman over a period of thirty-six years. With his meteoric rise coming at a time when attitudes toward Indians were predominantly negative, this manuscript explores the role of Saund’s Indian heritage in his journey to Congress and explains that Saund’s good works and commitment to U.S. values rather than his Indian background was responsible for his journey to Congress.
Keywords: 1956; Dalip Singh Saund; Indian-American; Indian immigration; Imperial County; Jacqueline Odlum